Management of Children with Glycogen Storage Disease (Liver Involvement Forms). Best Practice Guidelines - Alexander A. Baranov; Leyla S. Namazova-Baranova; Andrey N. Surkov; Olga S. Gundobina; Elena A. Vishneva; Tea V. Margieva; Nato D. Vashakmadze; Liliya R. Selimzyanova (Педиатрическая фармакология, 2020)
Glycogen storage disease is the hereditary carbohydrate metabolism pathology which is caused by mutations in various genes encoding enzymes responsible for glycogenesis and glycogenolysis. Excessive glycogen deposition in various tissues cells (mostly in liver and muscles) occurs due to enzyme defects. The authors present recent epidemiological data and features of glycogen storage disease etiology and pathogenesis. Clinical characteristics of different types of this disease are also presented. The data on laboratory-instrumental and morphological signs of glycogen storage disease in children, as well as data on its treatment methods is provided in accordance with the developed clinical guidelines. The article provides relevant information on disease types with predominant liver involvement, besides the variety of clinical forms of glycogenosis.